Etika dan Integritas Pilar Utama Pencegahan Korupsi di Lingkungan Kampus - Jesica Angel (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Ethics and integrity play a crucial role in creating an academic environment free from corrupt practices. As a center of learning, the campus should serve as a model for its students in upholding high moral and ethical standards. This article aims to highlight the importance of ethics and integrity as fundamental pillars in efforts to prevent corruption within the academic setting, such as on campus. Through a qualitative approach, data were collected from interviews with two campus workers—a canteen staff member and a parking attendant—who frequently interact indirectly with students and staff. These interviews explore their perspectives on the importance of being honest, responsible, and disciplined in their daily work. The findings show that even though they are not involved in academic activities, both workers contribute significantly to fostering an anti-corruption culture on campus. The canteen staff emphasized the importance of transparency in setting food prices to maintain students' trust, while the parking attendant stressed the need for discipline and order in managing the parking system to prevent irregularities. This article also examines how simple ethical behaviors, such as honesty in transactions and adherence to rules, can have a substantial impact on creating an integrity-driven campus environment. Therefore, the implementation of ethics and integrity is not solely the responsibility of academics but also of every element of the campus community without exception. In conclusion, strengthening the culture of ethics and integrity across all aspects of campus life is an essential part of a sustainable strategy to prevent corruption.